Development of a bi-layered cryogenic electrospun polylactic acid scaffold to study calcific aortic valve disease in a 3D co-culture model. (1st March 2022) - Stadelmann, Kathrin; Weghofer, Adrian; Urbanczyk, Max; Maulana, Tengku Ibrahim; Loskill, Peter; Jones, Peter D.; Schenke-Layland, Katja
Abstract: Calcified aortic valve disease (CAVD) is the most prevalent valve disease in the elderly. Targeted pharmacological therapies are limited since the underlying mechanisms of CAVD are not well understood. Appropriate 3D in vitro models could potentially improve our knowledge of the disease. Here, we developed a 3D in vitro aortic heart valve model that resembles the morphology of the valvular extracellular matrix and mimics the mechanical and physiological behavior of the native aortic valve fibrosa and spongiosa. We employed cryogenic electrospinning to engineer a bi-layered cryogenic electrospun scaffold (BCES) with defined morphologies that allowed valvular endothelial cell (VEC) adherence and valvular interstitial cell (VIC) ingrowth into the scaffold. Using a self-designed cell culture insert allowed us to establish the valvular co-culture simultaneously by seeding VICs on one side and VECs on the other side of the electrospun scaffold. Proof-of-principle calcification studies were successfully performed using an established osteogenic culture protocol and the here designed 3D in vitro aortic heart valve model. Statement of Significance: Three-dimensional (3D) electrospun scaffolds are widely used for soft tissue engineering since they mimic the morphology of the native extracellular matrix. Several studies have shown that cells behave more naturally on 3D materials than on the commonly used stiff two-dimensional (2D) cell culture substrates, which have no biological properties. As appropriate 3D models for the study of aortic valve diseases are limited, we developed a novel bi-layered 3D in vitro test system by using the versatile technique of cryogenic electrospinning in combination with the influence of different solvents to mimic the morphology, mechanical, and cellular distribution of a native aortic heart valve leaflet. This 3D in vitro model can be used to study valve biology and heart valve-impacting diseases such as calcification to elucidate therapeutic targets. Graphical abstract: Image, graphical abstract